MANAJEMEN PERENCANAAN PEMBELAJARAN GURU PAI DALAM MENINGKATKAN KUALITAS HASIL BELAJAR SISWA DI SD KOTA SOLOK - Syamsiwarti Syamsiwarti (IAIN Batusangkar, 2016)
Planning provides a wide range of decisions and explanations of the purpose, policy, program determination, methods and specific procedures. This qualitative study aimed at describing the instructional planning management of Islamic education on upgrading students’ achievement in Primary School Kota Solok. The intruments in this study were interview, observation and documentation. The results revealed that the teachers did make sylabus; annual program; semester program; efeective days; lesson plan; minimum standard criteria; and educational calendar. The teachers also did cooperation with the parents to upgrade students’ achievement. They had an obstacle on assessing students especially on guide book; information; managing time schedule; media; test instrument and lot of material.Keywords: Management, Instructional Planning, Teacher, Islamic Education, Learning Outcomes